2014
DOI: 10.2106/jbjs.m.00798
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Anatomic Investigation of the Lateral Ankle Ligaments for Surgical Reconstruction Procedures

Abstract: Footprint center distances from surgically relevant osseous landmarks identified in this study can be used during reconstructive surgery of the lateral ankle ligaments and may result in more anatomically accurate placement of the reconstructed ligaments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
121
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(127 citation statements)
references
References 41 publications
5
121
0
1
Order By: Relevance
“…We suggest the length measured by "centre to centre" distance would provide the best measurement to allow reconstruction surgery that requires bone tunnels at the anatomical origins and insertions of the ATFL and CFL. Neuschwander et al [26] and Clanton et al [6] reported the "centre to centre" distance, and it showed that the ATFL was around 17 mm long and the CFL was about 25 mm long.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest the length measured by "centre to centre" distance would provide the best measurement to allow reconstruction surgery that requires bone tunnels at the anatomical origins and insertions of the ATFL and CFL. Neuschwander et al [26] and Clanton et al [6] reported the "centre to centre" distance, and it showed that the ATFL was around 17 mm long and the CFL was about 25 mm long.…”
Section: Discussionmentioning
confidence: 99%
“…Burks and Morgan [18], Sindel et al [29] and Taser et al [11] report the distance between the midfibular insertion and lateral malleolar tip as 10 mm, 10.0 mm and 13.3 mm respectively. Clanton et al [36] reported that the distance between proximal insertion of single ATFL, superior band of ATFL and IATFL and the inferior tip of the lateral malleolus as 13.8 mm, 16.3 mm and 10.2 mm respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies give the distance between the ATFL mid-distal attachment and the subtalar joint as 18 mm [18] and 14.2 mm [25], while Taser et al [11] reported the distance between the mid-distal attachment and superior and inferior surfaces of the talus as 14.77 mm and 17.03 mm respectively. Clanton et al [36] identified the distal insertion of ATFL (single band) to be 11.3 mm to the anterolateral corner of trochlea of the talus and 17.8 mm to the apex of lateral talar process. Knowing the precise ATFL attachments to the talus should aid ligament reconstruction, as well as provide a better understanding of ATFL function in its role stabilising the ankle joint.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25][26][27] The described implant can be considered reliable and user-friendly. It also avoids bulky knots, 4,14 which are another possible source of complaints.…”
Section: Discussionmentioning
confidence: 97%